Joint ownership by farmers and investors in the agri-food industry: An exploratory study of the limited cooperative association - Jasper Grashuis (Agricultural and Food Economics, 2018)
Since the 1990s, producers of farm commodities have been attempting to enter value-added agri-food sectors by means of joint ownership of hybrid cooperatives. New generation cooperatives, characterized by substantial supply and equity requirements, inspired much farm producer optimism before revealing weaknesses and limitations in the early 2000s. In response, recent innovations in US cooperative state law introduced the limited cooperative association (LCA), a new legal entity allowing joint ownership by member patrons and member investors to facilitate large-scale equity acquisition. However, business registration data indicate few such organizations have been formed in the agri-food industry. The LCA is adopted by several small-scale operations in niche markets such as lamb, elderberry, and non-GMO seed, but there is not much interest among business organizations in the commodity sector. This paper raises possible explanations for the limited adoption of the LCA, including the competing objectives of farmers and investors, the ambiguous legal interpretation of investor objectives, the superiority of other legal structures, and the lack of strategic advantages. The conclusion facilitates an invitation to further study the challenging future of farmer cooperatives in the agri-food industry.
Keywords: D23; D71; L23; M13; Q13; 330; Agricultural cooperative; Ownership structure; Property rights; Limited cooperative association